Działalność Komisji Lordów Artykułów jako forma kontroli władzy królewskiej nad szkockim Parlamentem - Szymura, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The purpose of this paper is to show the functioning of the Scottish Parliament's special body, the Committee of Lords of the Articles. Committee, that operated between the 14th and 17th centuries, was a body made up of representatives of the Estates of the Kingdom of Scotland, whose task was to decide which of the petitions submitted to it would take the form of draft legislation and become the subject of legislative work. The main thesis of the paper is that the royal authority has had an increasing influence on the process of selecting the members of the Committee, which has resulted in the latter being transformed from a body designed to streamline legislative work into a censorship committee responsible for deciding on the agenda for the Parliament.
Keywords: Scots law; mixed jurisdiction; Lords of Articles; parliamentarianism